Indonesia' Capital City (Jakarta) Image on National and Internasional Media - Muchammad Nasucha; Mohamad Ghozali Moenawar; Gusmia Arianti; Michal Grzegorzewski (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The centrality of media amid society has been interrupted by gigantic impact of the internet nowadays. Departing from Lippman’s proposition, the foundation of agenda-setting theory with ecological online sphere consideration, and Galtung’s and devotees’ thought about international media works this research comparing national and international media Jakarta’s image as the capital city of Indonesia. Nevertheless, this essential topic seems neglected by previous research. This study used post-positivism paradigm, mixed-data with content analysis method, online observation. The sample of news taken randomly from the significant media according to pressgazette.co.uk for international media (6 media of 50), for Indonesia media was 4 of top 10 media. The selected news portal observed. The displayed news collected, structured, afterward analyzed systematically, objectively, from the title, paragraph, to the picture if any. The data shows both national and international media frame Jakarta’s image differently. International media portray Jakarta in negative way which is in line with Galtung’s and his devotee’s argument, appears as the third world country, framed with the negative attributes and tones as the most polluted city, sinking city, even dangerous city as the residence, workspace, and others. While major national media present Jakarta favorably as the central of national bustles in economy, business, education, and so forth, except one media reported Jakarta in deleterious way. This means the image of thing (capital city) related tightly to the interests or determining factors of media, while international media more complex layers than national media.